1985
DOI: 10.4098/at.arch.85-15
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the effects of variation at the transferrin locus on reproductive processes in deer mice

Abstract: ., 1985: Studies of the effects of variation at} the transferrin locus on reproductive processes in deer mice. Acta theriol., 30, 13: 227-240 [With 7 Tables & 1 Fig.] The pattern of inheritance and function of variation at the transferrin locus of deer mice, Peromyscus maniculatus (Hoy et Kennicott, 1857), were assessed in several studies. Despite substantial evidence of such function in other species, consequences of variation at this locus in deer mice were minimal. There was an underrepresentation of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…It is also noteworthy that Gulyaeva and Olenev's (1979) and McGovern and Tracy's (1981) results are not consistent with extensive mating data on the transferrin system in Cletnrionomys, Microtus, Peromyscus and Mus species (see e.g. Maurer 1967, Tamarin and Krebs 1969, Canham and Cameron 1972, Griswold and Dawson 1971, Dewsbury 1985, and Ashton and Dennis 1971. In my study, no differences were found in transferrin electromorphs of A. f.auicollis females in different phases of the reproductive period, and all genotypes found in this population occurred both in females and males.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…It is also noteworthy that Gulyaeva and Olenev's (1979) and McGovern and Tracy's (1981) results are not consistent with extensive mating data on the transferrin system in Cletnrionomys, Microtus, Peromyscus and Mus species (see e.g. Maurer 1967, Tamarin and Krebs 1969, Canham and Cameron 1972, Griswold and Dawson 1971, Dewsbury 1985, and Ashton and Dennis 1971. In my study, no differences were found in transferrin electromorphs of A. f.auicollis females in different phases of the reproductive period, and all genotypes found in this population occurred both in females and males.…”
Section: Discussioncontrasting
confidence: 40%
“…: Microtus pennsylvanicus, M. ochrogaster, M. townsendii (Maurer 1967, Tamarin and Krebs 1969, Clethrionomys rutilus, C. gapperi (Canham and Cameron 1972), Peromyscus polionotus (Griswold and Dawson 1971) Peromyscus maniculatus (Dewsbury 1985), Mus musculus (Ashton and Dennis 1970). All these results suggest that transferrin variation is genetically controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Although all mice were of proven fertilityand the first femalesreceived a mean of 4.9 ejaculations, only 60% delivered litters. This rate is not atypicalfor this species with females in cyclingestrus (e.g., Dewsbury, 1984). That this is not a functionof husbandry conditions is suggested by the high rate when females are in postpartum estrus (Dewsbury, 1979b).…”
Section: Discussionmentioning
confidence: 93%
“…Males of many rodent species display multiple intromissions prior to ejaculation. Several changes in the pattern of this behavior, the most reliable of which is an increase in the number of intromissions prior to ejaculation, may occur when males mate with recently mated, as opposed to unmated, females (e.g., Dewsbury, , 1985. These changes are consistent with the proposal that one function of the multiple intromissions may be related to cleansing of the female reproductive tract of material from previous males, so that a given male may deposit sperm and a copulatory plug most effectively (Dews bury , 1981).…”
Section: Sperm Competition and Effects Of Mating Order On Copulatory mentioning
confidence: 99%
“…Wood shavings were provided as bedding, and water and Purina laboratory rodent chow and lettuce supplements were provided. All the animals were known to be homozygous for one of the two alleles (slow or fast), affecting the rate of migration of transferrin (Trf) as determined by horizontal starch-gel electrophoresis (see Dewsbury, 1985). These will be referred to as "S" and "F" males and females.…”
Section: Subjectsmentioning
confidence: 99%